2013
DOI: 10.1002/wrcr.20132
|View full text |Cite
|
Sign up to set email alerts
|

Solute transport in fractured rocks with stagnant water zone and rock matrix composed of different geological layers—Model development and simulations

Abstract: [1] A model is developed to describe solute transport and retention in fractured rocks. It accounts for the fact that solutes can not only diffuse directly from the flowing channel into the adjacent rock matrix composed of different geological layers but also at first diffuse into the stagnant water zone occupied in part of the fracture and then from there into the rock matrix adjacent to it. In spite of the complexities of the system, it is shown that the analytical solution to the Laplace-transformed concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Shahkarami et al (2015) and Mahmoudzadeh et al (2013). It suffices, however, for the need in the analysis of field tracer tests, and should be taken as the starting point before going deeper into complicated systems involving, e.g.…”
Section: Mathematical Model and Solution Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…Shahkarami et al (2015) and Mahmoudzadeh et al (2013). It suffices, however, for the need in the analysis of field tracer tests, and should be taken as the starting point before going deeper into complicated systems involving, e.g.…”
Section: Mathematical Model and Solution Proceduresmentioning
confidence: 99%
“…with the material property group for the rock matrix given by (Mahmoudzadeh et al 2013(Mahmoudzadeh et al , 2016)…”
Section: Mathematical Model and Solution Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…It is expected that these regions contain the stressed crystals, whereas in the channels where water flows there are few, if any, stressed crystals. Until recently, Neretnieks [24] and Mahmoudzadeh et al [25] took the influence of the stagnant water zone in fracture plane into account. They found that solute diffusion into the stagnant water zone adjacent to the flow channel can significantly contribute to the retardation of solute.…”
Section: Introductionmentioning
confidence: 99%